Identifying the benefits of recovery programs of aquatic gymnastics, aquatic ludotherapy and therapeutic swimming on human motor, kinetotherapeutic and mental capacity - Badau Dana; Badau Adela (Helyion, 2024)
Introduction: This study aimed to evaluate the motor, kinetotherapeutic, and psychological benefits of three aquatic therapeutic programs-aquagym recovery (AG), aquatic ludotherapy (ALT), and therapeutic swimming (TS)-for students specializing in balneo-physio-kinetotherapy. Methods: The study group consisted of 101 students, out of which 43 students from the balneo-physiokinetotherapy study program (BFKT) and 67 master's degree students from physical therapy and functional rehabilitation (PTFR). The questionnaire was named Questionnaire regarding the benefits of therapeutic aquatic programs (QBTAP), and included 3 subscales according to the typology of the targeted objectives, namely: motor, kinetotherapeutic and psychological. The items of each subscale correspond to the objectives identified in the content of the 3 aquatic programs stipulated in the content of the courses corresponding to the disciplines in the education plans of academic study programs (BFK, TRFR). The motor subscale included 8 items, the kinetotherapeutic subscale included 16 items, and the psychological subscale included 10 items. The evaluation of the QBTAP questionnaire 5-point Likert scale. The three evaluated programs were: recovery aquagym (AG), aquatic ludotherapy (ALT) and therapeutic swimming (TS). Results: The results and conclusion sections should highlight the main findings succinctly. For example: "The QBTAP showed high internal consistency (Cronbach's Alpha >0.9) across all subscales and programs, with significant differences identified between the three programs (p < 0.05). Conclusion: The study concludes that aquagym most effectively improves motor capacity, aquatic ludotherapy enhances psychological function, and therapeutic swimming is most beneficial for recovery and rehabilitation.
Keywords: Aqua exercises programs; Aquatic gymnastics; Aquatic ludotherapy; Kinetotherapeutic rehabilitation; Mental capacity; Motor capacity; Promoting health; Therapeutic swimming.